2007
DOI: 10.1007/s10792-007-9091-4
|View full text |Cite
|
Sign up to set email alerts
|

Primary single-plate Molteno tube implantation for management of glaucoma in children with Sturge-Weber syndrome

Abstract: Outcomes of this small case study reveal that primary single-plate Molteno tube implantation appears to be associated with a limited success rate and a relatively high complication rate in eyes of children with glaucoma resulting from Sturge-Weber syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 22 publications
0
15
0
3
Order By: Relevance
“…; Olsen et al ; Zografos et al ; Irkeç et al ; Mandal ; Taylor et al ; Budenz et al ; van Emelen et al , Rumen et al. ; Höcht et al ; Amini et al ; Horgan et al ; Sharan et al , Chan et al ; Conway & Hosking ; Khitri et al ; Saltzmann et al , Kubicka‐Trząska et al ).…”
Section: Resultsunclassified
“…; Olsen et al ; Zografos et al ; Irkeç et al ; Mandal ; Taylor et al ; Budenz et al ; van Emelen et al , Rumen et al. ; Höcht et al ; Amini et al ; Horgan et al ; Sharan et al , Chan et al ; Conway & Hosking ; Khitri et al ; Saltzmann et al , Kubicka‐Trząska et al ).…”
Section: Resultsunclassified
“…The Molteno tube has also been used in a small case series in children suffering from SWS. Though the outcomes were not favourable and there was as an elevated complication rate [ 62 ].…”
Section: Sturge-weber Syndromementioning
confidence: 99%
“…Hamush et al reported choroidal detachment in 3 eyes of 11 patients [ 62 ]. Amini et al reported 3 cases of choroidal detachment in 9 patients with Sturge-Weber related glaucoma who underwent Ahmed valve implantation [ 63 ]. Budenz et al reported a serous choroidal detachment in two patients of 9 patients (20%) which underwent Baerveldt valve implant resolved spontaneously without the need to drain, the self-limiting nature of this complacence was due to prophylactic posterior sclerotomies performed, in more than one quadrant [ 64 ].…”
Section: Angle Surgery: Goniotomy and Trabeculotomymentioning
confidence: 99%